2000
DOI: 10.1111/j.1469-7793.2000.00077.x
|View full text |Cite
|
Sign up to set email alerts
|

ATP stimulates Cl secretion and reduces amiloride‐sensitive Na+ absorption in M‐1 mouse cortical collecting duct cells

Abstract: Using equivalent short circuit current (ISC) measurements we examined the effect of extracellular ATP on transepithelial ion transport in M‐1 mouse cortical collecting duct cells. Apical addition of ATP produced a rapid transient peak increase in ISC. This was followed by a fall below basal ISC due to a reduction in the amiloride‐sensitive ISC component. The ATP‐induced ISC increase was preserved in the presence of apical amiloride while it was reduced in the absence of extracellular Cl− and in the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
112
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(123 citation statements)
references
References 50 publications
10
112
1
Order By: Relevance
“…Positive immunofluorescence was also seen for ␣-, ␤-, and ␥-ENaC subunits in the CD of both Na ϩ -replete and Na ϩ -restricted rats; this immunofluorescence appeared stronger in the PC of Na ϩ -restricted rats. With respect to PC only, in Na ϩ -replete rats strong immunostaining for P2X 4 and 6 and for P2Y 4 , 6 , and 11 was consistently observed in the apical domain of PC throughout the CD, and weaker apical staining was also seen for P2X 2 and P2Y 2 (both localized to the medullary CD only) and ␣-ENaC. Strong basolateral immunostaining for P2X 4 and 6 was seen in all PC; basolateral staining for P2Y 2 was evident only in medullary CD PC.…”
Section: Urinary Namentioning
confidence: 99%
See 2 more Smart Citations
“…Positive immunofluorescence was also seen for ␣-, ␤-, and ␥-ENaC subunits in the CD of both Na ϩ -replete and Na ϩ -restricted rats; this immunofluorescence appeared stronger in the PC of Na ϩ -restricted rats. With respect to PC only, in Na ϩ -replete rats strong immunostaining for P2X 4 and 6 and for P2Y 4 , 6 , and 11 was consistently observed in the apical domain of PC throughout the CD, and weaker apical staining was also seen for P2X 2 and P2Y 2 (both localized to the medullary CD only) and ␣-ENaC. Strong basolateral immunostaining for P2X 4 and 6 was seen in all PC; basolateral staining for P2Y 2 was evident only in medullary CD PC.…”
Section: Urinary Namentioning
confidence: 99%
“…It has already been established that the activation of apically expressed P2R by extracellular nucleotides can decrease I am-s amplitude in the CD, [11][12][13][14][17][18][19] but argument remains over the P2R subtype(s) responsible. Previous pharmacologic profiling studies using mouse isolated CD reported that apical G protein-coupled P2Y 2 -like receptors mediated ATP-evoked inhibition of ENaC activity.…”
Section: P2 Receptor-mediated Inhibition Of I Am-s Amplitudementioning
confidence: 99%
See 1 more Smart Citation
“…In turn, raised [Ca 2+ ] int resulted in the activation of PKC which was proposed to mediate the inhibition of ENaC in rabbit CD cells. UTP inhibition of sodium transport was also confirmed in the mouse M1 collecting duct (CD) cell line [31] and in mouseisolated CDs [32]. Curiously, the early data of Cuffe et al…”
Section: Enac Modulation By P2rs In the Kidneymentioning
confidence: 82%
“…receptors have been detected in C11 cells (22). In addition, it was shown that extracellular ATP stimulates Cl -secretion while increasing cell Ca 2+ in both renal and digestive epithelial cells (20,23). The activation of Clconductance may modulate H + -ATPase in C11 cells.…”
Section: Resultsmentioning
confidence: 99%